Pengolahan Limbah Cair Sawit Dengan Metode Aop (Advanced Oxidation Process) Menggunakan Katalis LaMnO3 Perovskite Dan Oksidan Peroxymonosulfate - M Arief Riandy; Edy Saputra; Jhon Armedi Pinem (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Processing of palm oil into Crude Palm Oil (CPO) will produce a large amount of liquid waste. To produce a ton of crude palm oil (CPO) produced 6 m3 of palm oil mill effluent. In this study, a process for removing organic compounds in wastewater using the advanced oxidation process by combining peroxymonosulfate (2KHS5.KHSO4.K2SO4) and a catalyst of LaMnO3 Perovskite. The combination will produce sulfate free radicals that capable degrading harmful organic compounds in effluent effectively. Nanocrystalline LaMnO3 was obtained by calcination at a temperature of 800 °C for 2 hours with an average crystal diameter of the highest peak of 29 nm in the shape of the Rhombohedral catalyst and the catalyst has qualified the catalyst with a nanoparticle structure. Several variations of oxidation process variables were performed to assess their effect on organic matter decline. Some fixed variables were oxidation reaction temperature 30 oC, reaction time 120 min, stirring speed 400 rpm, and concentration of peroxymonosulfate solution 2 g/L, pH of liquid waste is 8 and catalyst concentration 0,4 g / L. Conclution of this research is efficiency of 80.5 % for decreasing COD and efficiency by 15,6% for TOC reduction. This proved that the LaMnO3 catalyst is capable of activating peroxymonosulfate.Keywords : AOP, LaMnO3 Perovskite, Oxidation, Peroxymonosulfate